1951
DOI: 10.3181/00379727-77-18741
|View full text |Cite
|
Sign up to set email alerts
|

Early Histological Changes Following Obstruction of Pancreatic Ducts in Dogs: Correlation with Serum Amylase

Abstract: 25178.1 mg, and 95.2, respectively. Three weeks after administration of glycine to these animals a mean fasting blood sugar of 101 mg was found. The same dose of insulin according to weight was then given and blood sugar determinations were made hourly. At the end of one hour the blood sugar was 39 mg. At the second, third, fourth, and fifth hours it was 37.4 ,mg, 48.5 mg, 63.5 mg, and 78.7 mg, respectively. This gives in rough figures a decrease of approximately 10 mg after the first hour and extending to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1954
1954
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…BOCHMAN et al (1971) showed that retrograde infusions of ferritin with a pressure of 150 mmHg into the canine pancreatic duct revealed accumulation of ferritin in a periacinar space, although the injection pressure used exceeded by far the 'resting' pressure of the duct. GIBBS and IVY (1951) showed that serum amylase rose twice as fast in the dogs when the pancreatic duct system was subjected to a pressure of 30 cm H2O after ligation of the pancreatic duct.…”
Section: Discussionmentioning
confidence: 99%
“…BOCHMAN et al (1971) showed that retrograde infusions of ferritin with a pressure of 150 mmHg into the canine pancreatic duct revealed accumulation of ferritin in a periacinar space, although the injection pressure used exceeded by far the 'resting' pressure of the duct. GIBBS and IVY (1951) showed that serum amylase rose twice as fast in the dogs when the pancreatic duct system was subjected to a pressure of 30 cm H2O after ligation of the pancreatic duct.…”
Section: Discussionmentioning
confidence: 99%
“…In early animal studies the serum amylase levels was shown to correlate with the histological changes of AP (16). However, the serum amylase levels have not been shown to correlate with severity of disease in human subjects and severity scores were developed based on markers of inflammatory response and complications in other organ systems.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Interestingly, serum amylase levels have long been used for AP diagnosis. Early animal studies showed that serum amylase levels were correlated with the histological changes of AP [ 23 ]. In the present study, we detected the level of serum amylase after rhein, honokiol, and rhein+honokiol treatment.…”
Section: Discussionmentioning
confidence: 99%